Recognition of Microcredentials in Higher Education: Challenges and Opportunities - Ergin, Hakan (International Higher Education, 2025)
Higher education is expected to prepare students with skills relevant to the job market. In response to this, policy makers have begun integrating microcredentials into degree programs. Microcredentials carry academic credits, distinguishing them from traditional short courses. Therefore, it is important to focus on microcredentials by trusted providers, ensuring quality assurance and portability. Their expanded use will undoubtedly enable students to flexibly acquire skills of their interest while pursuing a degree.